Métodos de mensuração de curvaturas radiculares e a influência do glide path na manutenção da centralização e no transporte apical preparos endodônticos : revisões sistemáticas e análise crítica - Hartmann, Rafael Chies (2018)
The great majority of the roots present curvatures and the knowledge of these curves allows the clinician a better choice for endodontic therapy. Therefore, it is necessary to use methods that can measure these curvatures with good accuracy levels. The preparation of a glide path prior to root canal instrumentation is widely suggested because can avoid possible operative errors, such as loss of centralization and apical transportation, especially in curved root canals. There is no consensus concerning the methods that can be used to measure radicular curvatures, nor regarding the efficacy of glide path. The present investigation has the objective of performing two systematic reviews in order to answer the following questions: 1- What are the methods, described in the literature, used to measure the angles and other characteristics of the curvatures of the root canals? 2- The glide path is able to reduce the apical transportation and the loss of centralization of the endodontic preparation? Also, how does the glide path - manual or engine-driven - result in minor operative errors? Methods: Using the appropriate terms for each review, electronic searches were performed on six databases: PubMed, PubMed Central (PMC), Embase, Scopus, EBSCO Dentistry & Oral Sciences Source (DOSS) and Virtual Health Library (VHL). We used studies published in English or in any language with Latin alphabet. There was no time limit for publications. In addition, in the second review, the included studies, the risk of biases was analyzed. Results: In review 1, about the methods of measurement of curvatures, 6,336 studies were obtained and of these, 31 articles that described innovative methods. Eleven studies described the methods used to measure only the angle of the radicular curvatures, for which they used 2D images. 13 studies also used 2D images, however, in addition to the angles, evaluated other features of the root canal curvatures (position, length, direction, height and shape). In addition, seven studies evaluated curvatures using 3D methods. In review 2, regarding glide path, 2,146 articles were obtained, and 18 studies fulfilled the inclusion criteria, composing the final analysis. 9 studies evaluated the glide path per se and 11 evaluated the impact of glide path on final engine-driven endodontic preparation. Conclusion: Revision 1 suggested that most methods for root canal curvature measurement have potential clinical applications; however, there is a lack of consensus on the ideal technique. In addition to the angle, other features, such as radius and position of curvature, need to be measured and should be considered when evaluating root canal curvature in both clinical and research purposes. Revision 2 revealed that engine-driven confection of glide path, when compared to manual, presents similar or better results of apical transportation and maintenance of root canal centralization. It was also observed that the preparation of glide path, prior to endodontic preparation, is associated with similar results or with a reduction of the apical transportation and the maintenance of the preparation centralization. It was also observed that deviations occur in all situations.